2019
DOI: 10.1177/1759720x19858514
|View full text |Cite
|
Sign up to set email alerts
|

Does periodontitis represent a risk factor for rheumatoid arthritis? A systematic review and meta-analysis

Abstract: Periodontitis is an inflammatory disease of dental supporting tissues (gingiva, periodontal ligament, and bone) and it has been suggested as a possible etiology for rheumatoid arthritis (RA). In this systematic review, we aim to verify if periodontitis represents a risk factor for RA. Electronic databases were consulted until March 2018 considering eligibility criteria focusing on: (P, participants) adults; (E, exposure) with periodontitis; (C, comparison) without periodontitis; and (O, outcome) development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 48 publications
(183 reference statements)
1
39
0
1
Order By: Relevance
“…In the present investigation, we verified that intense and sporadic alcohol intake promoted changes in quality and density of alveolar bone alone and in association with ligature-induced periodontitis. The 3 days On- 4 days-Off ethanol (3g/kg/day) protocol has been tested in animal model, the results demonstrated that it is a valid way to simulate binge drinking [ 24 26 ]. Binge drinking protocol has been widely used for investigation related to bone tissue alterations provoked by alcohol intake in a rat model.…”
Section: Discussionmentioning
confidence: 99%
“…In the present investigation, we verified that intense and sporadic alcohol intake promoted changes in quality and density of alveolar bone alone and in association with ligature-induced periodontitis. The 3 days On- 4 days-Off ethanol (3g/kg/day) protocol has been tested in animal model, the results demonstrated that it is a valid way to simulate binge drinking [ 24 26 ]. Binge drinking protocol has been widely used for investigation related to bone tissue alterations provoked by alcohol intake in a rat model.…”
Section: Discussionmentioning
confidence: 99%
“…As a chronic autoimmune disease, rheumatoid arthritis (RA) is characterized by persistent inflammatory synovitis and progressive degeneration of cartilage and bone. A meta-analysis found a higher RA prevalence in periodontitis patients compared with controls [ 142 ], and non-surgical periodontal therapy in individuals with RA and periodontitis was associated with improvements in markers of disease activity in RA [ 143 ]. Many periodontal bacteria, particularly P. gingivalis , were detected in synovial fluid from patients with RA at the DNA level (42.1%) [ 144 ].…”
Section: Rheumatologymentioning
confidence: 99%
“…Bidirectional interference has been also reported ( 7 ). The chronic bacterial challenge resulting from periodontitis is a persistent source of inflammatory mediators ( 8 ) that might interfere directly and indirectly in several systems ( 9 , 10 ) and promote effects in diabetes as insulin resistance, being able to increase the onset of diabetes complications ( 7 , 11 ).…”
Section: Introductionmentioning
confidence: 99%